Assessment of image quality using gadobenate dimeglumine and gadoxetic acid contrast agents for hepatocellular carcinoma evaluation in magnetic resonance liver imaging / Nur Syafiqah Abu Bakar, Fara Shuhaida Shafiee and Mohd Hafizi Mahmud - Mahmud, Mohd Hafizi; Abu Bakar, Nur Syafiqah; Shafiee, Fara Shuhaida (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Gadolinium-based contrast agent (GBCA) has a valuable role for optimizing the detection of lesions in contrast-enhanced Magnetic Resonance Imaging (MRI) examination. This study aimed to evaluate the image quality using liver specified GBCA; gadobenate dimeglumine and gadoxetic acid contrast agents for hepatocellular carcinoma (HCC) assessment in MR liver imaging. MR images of twenty-two (n=22) HCC patients who underwent either one of the liverspecified GBCA-enhanced MRI at 1.5T were retrospectively assessed. Qualitative and quantitative assessments were performed by three blinded review independent observers and by using image quality parameters; signal noise ratio (SNR) and contrast noise ratio (CNR), respectively between HCCs and liver parenchyma. Cohen's Kappa analysis showed that the inter-reviewer agreements of HCC presence and confidence level using gadobenate dimeglumine were "entirely agree" and "fairly disagree", respectively, while "fairly agree" and "moderately agree" were observed for gadoxetic acid, respectively. The SNR and CNR of both contrast enhanced images were not statistically significant each other (p > 0.05). Gadobenate dimeglumine-enhanced and gadoxetic acid-enhanced MR images had similar image quality for HCC assessment. The advantages of each contrast agents should be taken into consideration to optimize the detection and characterization of HCC in contrast-enhanced MR imaging for improved clinical management of HCC.